ANTIOXIDANT AND CYTOTOXIC ACTIVITIES OF THAI LOCAL PLANT EXTRACTS - Parkpoom, Thitima; Suksabye, Parinda; Parkpoom, Phot; Chantree, Kanlayaporn; Thummamikkapong, Sureeporn (Srinakharinwirot University Journal of Sciences and Technology, 2024)
The purpose of this study was to analyze the total phenolic, total flavonoids, antioxidant, cytotoxic activity and antioxidant components of crude extracts from eight species of Thai local plants using different solvents such as ethanol and hexane. Ethanol showed significantly higher percentage extraction yields than hexane. The contents of total phenolic and total flavonoids in the crude ethanol extract of Cyperus rotundus (CRE) were the highest at 11.617±0.289 mg GAE/g dry extract and 7.973±0.231 mg QE/g dry extract, respectively. The free radical scavenging of crude ethanol extracts of C. rotundus was the highest compared to the other plants and showed IC50 values in the DPPH assay and ABTS assay of 0.408±0.011 mg/ ml and 0.402±0.0071 mg/ml, respectively. Moreover, crude ethanol extracts of C. rotundus indicated the presence of catechin (m/z 289.1) and anthocyanin (m/z 463.2), as analyzed by the LC-MS method. The catechin content was important in corroborating antioxidant activity. Studies of the in vitro cytotoxic activity of the crude ethanol extracts of C. rotundus against the NCI-H187 cell line showed IC50 values of 42.47±2.66 µg/ml. In addition, the crude ethanol extract of Kaempferia parviflora against KB and NCI-H 187 cell lines showed IC50 values of 60.24±1.73 and 27.22±1.04 µg/ml, respectively. These results indicated that the traditional medicinal plants C. rotundus and K. parviflora are excellent sources of antioxidants and potential cytotoxic agents against KB and NCI-H 187 cell lines.